Modulation of serum albumin protein corona for exploring cellular behaviors of fattigation-platform nanoparticles - Nguyen, Van Hong; Meghani, Nilesh M.; Amin, Hardik H.; Tran, Thao T.D.; Tran, Phuong H.L.; Park, Chulhun; Lee, Beom Jin (Colloids and Surfaces B: Biointerfaces, 2018)
Albumin is the most abundant protein in blood, and is the most frequently identified protein in the protein corona of nanoparticles (NPs). Thus, albumin plays an important role in modulating NPs’ physicochemical properties and bioavailability. In this study, the effect of bovine serum albumin (BSA) on gelatin-oleic nanoparticles’ (GONs) physicochemical properties and cellular uptake were evaluated. Coumarin-6 was used as indicator to track the cellular uptake of GONs. The binding of BSA onto the GON surface increased the size, slightly reduced the negative net charge of the GON, and improved GON stability. The presence of BSA in cell culture media reduced the cellular uptake of BSA-uncoated GONs on human embryonic kidney cells 293 (HEK 293) and human adenocarcinoma alveolar basal epithelial cells (A549) in the media without FBS addition. Pre-coated BSA corona decreased cellular uptake of GONs in A549 cells in the media, with and without supplemented with 10% fetal bovine serum (FBS) but drastically increased cellular uptake on HEK 293 cells. BSA could be used to modulate protein corona as an endogenous ligand in NP design simply by mixing or incubating BSA with NPs before in vivo administration to inhibit or induce cellular uptake in specific cell types.
Keywords: Bovine serum albumins; Cellular uptake; Lung cancer cells; Protein coronas; Protein nanoparticles; Animals; Cattle; Cell Line, Tumor; HEK293 Cells; Humans; Nanoparticles; Particle Size; Protein Corona; Serum Albumin, Bovine; Surface Properties; Albumin-precoated nanoparticles; Bovine serum albumin; Cellular uptake; Gelatin-oleic nanoparticles; Lung cancer cells; Protein corona; Protein-nanoparticle interaction